Impact of short message service and peer navigation on linkage to care and antiretroviral therapy initiation in South Africa. (15th March 2023) - Lippman, Sheri A.; de Kadt, Julia; Ratlhagana, Mary J.; Agnew, Emily; Gilmore, Hailey; Sumitani, Jeri; Grignon, Jessica; Gutin, Sarah A.; Shade, Starley B.; Gilvydis, Jennifer M.; Tumbo, John; Barnhart, Scott; et al.
Abstract : Objective: We examine the efficacy of short message service (SMS) and SMS with peer navigation (SMS + PN) in improving linkage to HIV care and initiation of antiretroviral therapy (ART). Design: I-Care was a cluster randomized trial conducted in primary care facilities in North West Province, South Africa. The primary study outcome was retention in HIV care; this analysis includes secondary outcomes: linkage to care and ART initiation. Methods: Eighteen primary care clinics were randomized to automated SMS ( n  = 7), automated and tailored SMS + PN ( n  = 7), or standard of care (SOC; n  = 4). Recently HIV diagnosed adults ( n  = 752) were recruited from October 2014 to April 2015. Those not previously linked to care ( n  = 352) contributed data to this analysis. Data extracted from clinical records were used to assess the days that elapsed between diagnosis and linkage to care and ART initiation. Cox proportional hazards models and generalized estimating equations were employed to compare outcomes between trial arms, overall and stratified by sex and pregnancy status. Results: Overall, SMS ( n  = 132) and SMS + PN ( n  = 133) participants linked at 1.28 [95% confidence interval (CI): 1.01–1.61] and 1.60 (95% CI: 1.29–1.99) times the rate of SOC participants ( n  = 87), respectively. SMS + PN significantly improved time to ART initiation among non-pregnant women (hazards ratio: 1.68; 95% CI: 1.25–2.25) and men (hazards ratio: 1.83; 95% CI: 1.03–3.26) as compared with SOC. Conclusion: Results suggest SMS and peer navigation services significantly reduce time to linkage to HIV care in sub-Saharan Africa and that SMS + PN reduced time to ART initiation among men and non-pregnant women. Both should be considered candidates for integration into national programs. Trial registration: NCT02417233, registered 12 December 2014; closed to accrual 17 April 2015.